Interaksi dan Pemanfaatan Hasil Hutan oleh Masyarakat Sekitar Taman Nasional Gunung Leuser - Fahmi Fahmi; Agus Purwoko; Dodi Sumardi (Program studi Kehutanan USU, 2015)
Leuser National Park is a conservation area with saved abundant natural resources. The existence provide benefits for people living around. Where the community can utilize its natural wealth in order to meet the day-to-day life. This study aims to determine what types of forest products used by local communities and model/patern of interaction in their utilization. The method used combination of Documentation Study and Direct Methods with interview techniques and field observations. Data analysis was conducted descriptively to obtain representation of each desired goal. The results of this study indicated that forest products which used by the community around the Mount Leuser National Park were water, glugur acid (Garcinia atroviridis), sago palm leaves (Metroxylon sagu), kacer bird (Copsychus saularis), jurung fish (Tor soro), setekep plant (Elatostema umbellatum), tiga urat plant (Melastoma malabathricum), wood and firewood. Community interaction in the utilization of forest products occurs throughout the year but with different intensities.Keywords: Mount Leuser National Park, the utilization of forest products, interaction of forest communities